Oscillatory and anti-oscillatory motifs in genetic regulatory networks - 叶纬明 张朝阳 吕彬彬 狄增如 胡岗 刘东 银振强 王双 王粉梅 陈巍 韩正甫 (Chinese physics B, 2012)
Recently, self-sustained oscillatory genetic regulatory networks （GRNs） have attracted significant attention in the biological field. Given a GRN, it is important to anticipate whether the network could generate oscillation with proper parameters, and what the key ingredients for the oscillation are. In this paper the ranges of some function-related parameters which are favorable to sustained oscillations are considered. In particular, some oscillatory motifs appearing with high-frequency in most of the oscillatory GRNs are observed. Moreover, there are some anti-oscillatory motifs which have a strong oscillation repressing effect. Some conclusions analyzing these motif effects and constructing oscillatory GRNs are provided.